Variation in symptoms and morphology of Fusarium spp. on shallot associated with basal plate rot disease in Brebes District, Central Java Province, Indonesia - LISA MARIANAH; ABDJAD ASIH NAWANGSIH; ABDUL MUNIF; GIYANTO GIYANTO; EFI TODING TONDOK (Society for Indonesian Biodiversity, 2024)
Abstract. Marianah L, Nawangsih AA, Munif A, Giyanto, Tondok ET. 2024. Variation in symptoms and morphology of Fusarium spp. on shallot associated with basal plate rot disease in Brebes District, Central Java Province, Indonesia. Biodiversitas 25: 2198-2208. Basal plate rot disease is an important disease of shallots that causes losses in the field and storage. The disease is caused by Fusarium complex species, with different levels of virulence and host susceptibility. The six species of Fusarium spp. reported to cause basal plate rot disease of onion were F. oxysporum f.sp. cepae, F. proliferatum, F. redolens, F. solani, F. acutatum and F. tricinctum. Information about the variation in symptoms and morphology of fungi that cause basal plate rot disease on shallots, especially in Indonesia, is still very limited. Besides, the species that cause basal plate rot disease on shallots has not been molecularly confirmed using specific primers. The objective of this study was to isolate, identify, and study the variation in symptoms of the fungus associated with basal plate rot disease. The fungi were isolated from shallot plants symptomatic of basal plate rot disease collected from Brebes, Central Java Province. Eight isolates of Fusarium with different morphologies were successfully isolated and identified. Five isolates were identified as F. solani (isolate BC1, BC2, BC3, BBS1, and BBS4), two isolates as F. oxysporum f.sp. cepae (isolate BC4 and BBS6) and one isolate F. proliferatum (isolate BBS5). All eight isolates were pathogenic on shallots with different levels of virulence and symptom variations. BC4 isolate had the highest level of virulence, resulting in plant death, and was identified as F. oxysporum f.sp. cepae.